Plano de projeto: planejamento da implementação da ferramenta de manutenção produtiva total - Herbstrith, Vanessa Miranda (Universidade do Vale do Rio dos Sinos, 2012)
This Project aims to create a plan in which the methodology of TPM (Total Productive Maintenance) can be implemented in the company chosen for the research. It is the application of the methodology contained in the PMBOK guide, to structure the whole project, so, are minimized simple mistakes when it issue is project management. The implementation of TPM will be disclosed among the employees who will be of much importance. They will be actively part of this project, the largest involved, which are the own maintenance sector, which will benefit from restructuring and a new working methodology and injectors department that contribute to the reduction the stopped of machine and increasing their productivity. The product of this project aims to structure the maintenance of machines located in a specific unit.
Keywords: Gestão de projeto; TPM; Implementação; Project management; Implementation